KOMPOSISI FORAMINIFERA BENTIK BESAR PADA SEDIMEN MANGROVE - Gabriel F. Tulung; Jane M. Mamuaja; Royke M. Rampengan; Hermanto W. K. Manengkey; Rignolda Djamaluddin; Rene C. Kepel (Sam Ratulangi University, 2023)
Large benthic foraminifera are unicellular organisms that live at the surface of the sediments and have the ability to form shells of calcium carbonate (CaCO3). This research was conducted with the aim of describing and analyzing the composition of the large benthic foraminifera found in the coastal mangrove areas of Tasik Ria and Tongkeina. Sampling activities were carried out by taking sediment samples from mangrove areasTasik Ria and Tongkeina. The large benthic foraminifera identified were 3,680 specimens. Foraminifera species and genera obtained were 28 species from 15 genera in the mangrove sediments of Tasik Ria Beach and 23 species from 11 genera in the mangrove sediments of Tongkeina Beach. The dominant foraminifera genera with a proportion of more than 5% at both study sites were Ammonia, Amphistegina, Calcarina, Elphidium and Neorotalia. Based on the type of shells, foraminifera with light shells were more commonly found in the mangrove area of Tasik Ria than in Tongkeina. In contrast, more sandy-shelled foraminifera were found in the mangrove area of Tongkeina than in Tasik Ria. Furthermore, the Diversity Index for large benthic foraminifera obtained at both locations was in the medium category with values indicating the diversity of foraminifera species obtained in the mangrove area of the Tasik Ria coast was higher than the foraminifera obtained in the mangrove area of the Tongkeina coast. Keywords: Large Benthic Foraminifera, Mangrove Area, Tasik Ria Beach, Tongkeina BeachABSTRAKForaminifera bentik besar merupakan organisme uniseluler yang hidup di dasar perairan dan memiliki kemampuan membentuk cangkang dari zat kapur kalsium karbonat (CaCO3). Penelitian ini dilakukan dengan tujuan untuk mendeskripsikan dan menganalisis komposisi foraminifera bentik besar yang terdapat pada area mangrove pantai Tasik Ria dan Tongkeina. Metode yang digunakan dalam penelitian ini meliputi kegiatan pengambilan sampel hingga tahap identifikasi foraminifera bentik berukuran besar yang ditemukan pada sedimen mangrove pantai Tasik Ria dan pantai Tongkeina. Foraminifera bentik berukuran besar yang teridentifikasi adalah sebanyak 3.680 spesimen. Sejumlah 28 spesies dari 15 genus ditemukan pada sedimen mangrove Pantai Tasik Ria dan 23 spesies dari 11 genus pada sedimen mangrove Pantai Tongkeina. Genus foraminifera yang dominan dengan proporsi lebih dari 5% yang diperoleh pada lokasi penelitian adalahAmmonia, Amphistegina, Calcarina, Elphidium dan Neorotalia. Berdasarkan tipe cangkang, foraminifera bercangkang gampingan lebih banyak ditemukan di kawasan mangrove pantai Tasik Ria daripada di Tongkeina. Sebaliknya, foraminifera bercangkang pasiran lebih banyak ditemukan di kawasan mangrove pantai Tongkeina daripada Tasik Ria. Selanjutnya Indeks Keanekaragaman foraminifera bentik berukuran besar yang diperoleh pada kedua lokasi dikategorikan sedang dengan nilai yang diperoleh pada kawasan mangrove pantai Tasik Ria lebih tinggi dibandingkan kawasan mangrove pantai Tongkeina.Kata Kunci: Foraminifera Bentik Besar, Kawasan Mangrove, Pantai Tasik Ria, Pantai Tongkeina